Quantifying the benefits of building instruments to FEMA P-58 rapid post-earthquake damage and loss predictions. (1st December 2018) - Cremen, Gemma; Baker, Jack W.
Highlights: Prediction errors tend to decrease as the number of instruments increases. Errors are much lower when more than a small number of floors are instrumented. Errors may be highly dependent on the arrangement of instruments. The optimum arrangement of instruments depends on the prediction of interest. Abstract: Seismic instrumentation in a building is used to accurately capture its response during an earthquake, and so should enable enhanced rapid post-earthquake predictions of the event's consequences for the building (among other benefits). Such instrumentation is costly, however, thus it is useful to know the extent to which varying degrees of its implementation within a building affect the accuracy of these predictions. The purpose of this study is to develop a methodology for quantifying the errors in post-earthquake damage and loss consequence predictions calculated from the FEMA P-58 Seismic Performance Assessment procedure, when different numbers of building instruments are used to capture the response of a building in a given event. We use responses measured in instrumented buildings during the 1994 Northridge earthquake, and obtain consequence predictions via the FEMA P-58 methodology. The density of instrumentation examined ranges from the case in which all floors are instrumented to that in which no instrumentation is present and FEMA P-58 simplified procedures are used to predict response and corresponding consequences. We find that errors in consequence predictions decrease as the number of building instruments is increased and that the reduction in error is substantial as soon as more than a small number of floors are instrumented. This is valuable information for a building owner if they wish to use seismic instrumentation as a means of rapidly obtaining damage and loss information for post-earthquake decision-making.